Children's high-level writing skills: development of planning and revising and their contribution to writing quality - Teresa Limpo (2013)
Background: It is well established that the activity of producing a text is a complex one involving three main cognitive processes: Planning, translating, and revising. Although these processes are crucial in skilled writing, beginning and developing writers seem to struggle with them, mainly with planning and revising. Aims: To trace the development of the high-level writing processes of planning and revising, from Grades 4 to 9, and to examine whether these skills predict writing quality in younger and older students (Grades 4-6 vs. 7-9), after controlling for gender, school achievement, age, handwriting fluency, spelling, and text structure. Sample: Participants were 381 students from Grades 4 to 9 (age 9-15). Method: Students were asked to plan and write a story and to revise another story by detecting and correcting mechanical and substantive errors. Results: From Grades 4 to 9, we found a growing trend in students' ability to plan and revise despite the observed decreases and stationary periods from Grades 4 to 5 and 6 to 7. Moreover, whereas younger students' planning and revising skills made no contribution to the quality of their writing, in older students, these high-level skills contributed to writing quality above and beyond control predictors. Conclusion: The findings of this study seem to indicate that besides the increase in planning and revising, these skills are not fully operational in school-age children. Indeed, given the contribution of these high-level skills to older students' writing, supplementary instruction and practice should be provided from early on. (c) 2013 The British Psychological Society.